Penyuluhan Fisioterapi Komunitas dalam Penerapan Program Fisioterapi sebagai Upaya Pencegahan Frozen Shoulder pada pekerja Industri Arjosari Shuttlecock di Arjosari - Zazkia Amanda Putri Sania; Zidni Imanurrohmah Lubis; Fika Ertitri (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Shuttlecock industry workers in Arjosari Village perform many repetitive activities that involve intensive use of their upper extremities, putting them at high risk of musculoskeletal disorders, particularly frozen shoulder. This condition is characterized by pain, limited movement, and decreased shoulder function, which can interfere with work productivity. This community service activity was carried out through community physiotherapy counseling with a promotive and preventive approach, using leaflets, ergonomic education, and demonstrations of simple exercises such as cross-body arm stretches, pendulum exercises, arm circles, finger walk exercises, and towel exercises. The methods used included pre-tests, material delivery, exercise practice, discussions, and post-tests to assess knowledge improvement. The results of the activity showed that the majority of workers had experienced initial shoulder complaints, with a predominance of female respondents (93.33%). Average knowledge increased from 0% on the pre-test to 100% on the post-test. The counseling proved effective in increasing workers' understanding of frozen shoulder prevention, thereby reducing the risk of shoulder pain and increasing work productivity